The impact of caregiving on the roles and valued activities of stroke carers: A systematic review of qualitative studies. - Melissa Jammal; Gregory S Kolt; Karen P Y Liu; Nariman Dennaoui; Emma S George (PLoS ONE, 2024)
Objective To understand the experiences of informal carers and the impact of role and activity changes on their health and wellbeing. Methods A systematic search of CINHAL, MEDLINE, Embase, APA PsycInfo, and Web of Science was conducted. Studies were eligible if they included informal stroke carers (≥18 years), used a qualitative methodology, explored the roles and valued activities of stroke carers, and were published in English. The 10-item Critical Appraisal Skills Programme checklist for qualitative studies was used to assess methodological quality. The results of the included studies were thematically synthesised. Results A total of 36 qualitative studies were included and four overarching themes were identified: (1) Life adjustment; (2) Changing role and identity; (3) Changing activities: From meaningful to purposeful; and (4) Understanding and supporting carers. Conclusion The sudden nature of stroke requires major readjustment in the carers life that has implications on their relationships, roles, and activities, subsequently impacting on their health and wellbeing. Health professionals and researchers should collaborate with stroke carers to identify their valued activities and implement realistic strategies to maintain these activities. Future interventions designed for carers should implement education about the importance of participating in valued activities and strategies to maintain these activities.